Illuminating the dynamics of signal integration in Natural Killer cells - Pageon, Sophie V.; Rudnicka, Dominika; Davis, Daniel M. (Frontiers in Immunology, 2012)
Natural Killer (NK) cell responses are shaped by the integration of signals transduced from multiple activating and inhibitory receptors at their surface. Biochemical and genetic approaches have identified most of the key proteins involved in signal integration but a major challenge remains in understanding how the spatial and temporal dynamics of their interactions lead to NK cells responding appropriately when encountering ligands on target cells. Well over a decade of research using fluorescence microscopy has revealed much about the architecture of the NK cell immune synapse – the structured interface between NK cells and target cells - and how it varies when inhibition or activation is the outcome of signal integration. However, key questions – such as the proximity of individual activating and inhibitory receptors – have remained unanswered because the resolution of optical microscopy has been insufficient, being limited by diffraction. Recent developments in fluorescence microscopy have broken this limit, seeding new opportunities for studying the nanometre-scale organisation of the NK cell immune synapse. Here, we discuss how these new imaging technologies, including super-resolution imaging and other novel light-based methods, can illuminate our understanding of NK cell biology.